2009
DOI: 10.1073/pnas.0904877106
|View full text |Cite
|
Sign up to set email alerts
|

Specific Arabidopsis HSP90.2 alleles recapitulate RAR1 cochaperone function in plant NB-LRR disease resistance protein regulation

Abstract: Both plants and animals require the activity of proteins containing nucleotide binding (NB) domain and leucine-rich repeat (LRR)domains for proper immune system function. NB-LRR proteins in plants (NLR proteins in animals) also require conserved regulation via the proteins SGT1 and cytosolic HSP90. RAR1, a protein specifically required for plant innate immunity, interacts with SGT1 and HSP90 to maintain proper NB-LRR protein steady-state levels. Here, we present the identification and characterization of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 39 publications
3
103
0
Order By: Relevance
“…Both interacting proteins might be involved in building a recognition complex that consists of R and RAR1 proteins and recognized effectors [95,96]. Interestingly, it was recently discovered that in Arabidopsis, specific mutations in HSP90, referred as hsp90.2, suppress the rar1 mutation and restore the accumulation and function of R proteins [97]. It was observed that SGT1 interacts with another co-chaperone, HSC70, in both the nucleus and cytosol.…”
Section: R Proteins-mediated Signaling Pathwaymentioning
confidence: 99%
“…Both interacting proteins might be involved in building a recognition complex that consists of R and RAR1 proteins and recognized effectors [95,96]. Interestingly, it was recently discovered that in Arabidopsis, specific mutations in HSP90, referred as hsp90.2, suppress the rar1 mutation and restore the accumulation and function of R proteins [97]. It was observed that SGT1 interacts with another co-chaperone, HSC70, in both the nucleus and cytosol.…”
Section: R Proteins-mediated Signaling Pathwaymentioning
confidence: 99%
“…HSP90 acts as a dimer and in an ATPase-dependent cycle alternately complexes with and separates from additional factors and cochaperones to effect a kinetically dynamic process of client protein maturation. In plants, HSP90 is best characterized as associating with the cochaperone SGT1 to stabilize NLR proteins, which mediate plant defense mechanisms (28)(29)(30). Additionally, HSP90 is important in phenotypic plasticity, developmental stability, and buffering of genetic variation (31)(32)(33).…”
mentioning
confidence: 99%
“…ATP-dependent Hsp70 chaperones, originally discovered in Drosophila as "puffing pattern" (Ritossa 1962(Ritossa , 1996, are known to be associated with numerous cellular roles like protein translation and translocation, protein folding or chaperoning, suppression of aggregation and re-activation of denatured proteins (Zhang et al 2005;Hubert et al 2009). Plant Hsp70s, together with their cochaperones DnaJ/Hsp40 and GrpE, are localised in the cytosol, endoplasmic reticulum, mitochondria, chloroplasts, and peroxisomes (Vierling 1991;Boston et al 1996;Bukau & Horwich 1998).…”
mentioning
confidence: 99%